Community acceptance of vertical farming in urban high-density areas of Kuala Lumpur, Malaysia - Kalantari, Fatemeh (2019)
Three significant challenges humanity faces today include the ever-expanding population, food security, and environmental degradation. It is, therefore, becoming increasingly necessary to study how to plant and grow crops via controlled environment agriculture inside multi-storied buildings in urban areas. This practice is termed Vertical Farming (VF). VF offers an innovative solution to the three challenges described above by allowing for farming in high-rise buildings in populous cities. Surprisingly, however, no VF structure has been built in Malaysia. Furthermore, there is a lack of existing academic research concerning the community acceptance of VF as new technology. Therefore, this study aims to assess the community acceptance of VF in the urban, high-density areas of Kuala Lumpur (KL). Eight factors of community acceptance were derived from the literature review, and the research model was designed along with the hypotheses and methodology to investigate these factors. The results obtained and presented in this research were based on interviews with experts as well as a questionnaire survey. The data collected from the 403 participants were used to form the survey. SPSS20 was used to analyze the data in Windows. Based on the findings, Concern, Location, Demographic characteristics, Value and Belief, Trust, Fairness, and Knowledge are factors that impact the Community Acceptance of VF in urban high-density areas in KL. Descriptive statistics indicate that more than 70% of the participants do not have any experience or knowledge of VF. However, 61.7% of participants would be open to VF development in urban high-density areas in KL. In general, participants agreed with the benefit factor followed by Location, Concern, and Value and Belief. In other words, residents in KL showed a low level of NIMBY syndrome. Age was the only significant factor with regard to the level of community acceptance. Overall, participants perceived the community as a more honest developer, but they believed the government as a suitable developer. Also, they often got very pessimistic toward private developers. There were significant positive correlations among factors, with the only negative correlation being concern and location. Furthermore, significant positive correlations were found between factors and community acceptance. Only the correlation between concern and community acceptance was negative. The regression test presented the highest effect on community acceptance belongs to the Location, benefit & Concern factors, respectively. The findings of this study could positively contribute to knowledge generation, stakeholder network establishment, new project implementation, and improvement of the general perception of VF innovation. Additionally, the proposed theoretical framework offers a notable increase in the ability to predict intentions and subsequent behaviors of the community acceptance of VF.